Representações sociais de idosos e cuidadores sobre a doença de Alzheimer - Queiroz, Ronaldo Bezerra de (2016)
In medical practice it has been observed that elderly people have a concern about Alzheimer's disease (AD) that can influence their mode or quality of life. The patient with AD will inevitably need a caregiver and this activity is permeated by difficulties that with time can induce changes in their health. The theory of social representations is a form of knowledge and a reality understanding system that organize the individual's relations with the world and guide their conduct and behavior in the social environment, allowing people how to think and behave facing conflicting phenomena in their daily lives. Objective: To identify social representations of Alzheimer's disease built for elderly people without AD. To know the social representations built by caregivers of patients with Alzheimer's disease and to explore the social representations of Alzheimer's disease according to caregivers and elderly people without Alzheimer's disease. Methodology: It is an exploratory research on a qualitative approach. Regarding to the ethical aspects the project was submitted to the Research Ethics Committee of the University Hospital Lauro Wanderley the Federal University of Paraíba and approved under paragraph. 574,968 of 03/31/2014, CAAE-27670714.4.0000.5183. The sample for convenience with 50 caregivers of elderly with Alzheimer's disease and 50 elderly people without this disease, of both sexes, who answered a semi-structured interview. The collected data were organized in a corpus, processed by IRAMUTEQ software and interpreted according to the theoretical framework of social representations. Results: The results obtained after analysis delineated three articles: the first is an integrative review of the literature on the perception of older people about AD that signaled the need to develop studies with the theoretical framework of social representations. The second article discusses the social representations built by elderly people without Alzheimer's disease about Alzheimer's disease, in this article, the elderly talk about the AD; the third article identifies the social representations built by caregivers of patients with Alzheimer's disease, the caregivers talk about the AD. Final Thoughts: The social representations by caregivers of people with AD presented subjective dimensions with positive and negative content. The social representations captured in the speeches of the elderly were different but had similar content to describe the disease, they expressed feelings of sadness in many situations, as well as observe these feelings in the family involved. The behavior of elderly people with the disease verbalizing words aggressively influences the act of caring, leaving the caregivers stressed. The degree of dependency in their care associated with abandonment by family and friends of the elderly have implications for the lifestyle of the familiar caregiver who has to devote harder to their work, and on the other hand, when associated with financial restrictions they also abandon leisure. Positive aspects were reported as personal and emotional growth developed in care. This study contributes to reflection and subsidy for the development of public policies for the elderly and caregivers, as well as a stimulus to increase professional training to the needs brought about Alzheimer's disease.